Bangladeshi Female Graduate Doctors Leaving Medical Profession: A Real Threat to Health System or a Rumor (Bangladesh Journal of Medical Education, 2025)
Background: Female graduate doctors represent a major part of health care/ educational services in Bangladesh. But a portion of female graduate doctors leaving their profession immediately or after sometimes of completion of their graduation, even some of them never registered themselves under Bangladesh Medical & Dental Council (BM&DC). Objective: This research aimed to find out percentages of female graduate doctors leaving medical profession and different reasons behind it.  Methods: This cross sectional descriptive research was carried out in the Centre for Medical Education (CME), Mohakhali, Dhaka from July 2022 to June 2023. Data were collected through one self-administered semi-structured questionnaire among 500 female graduate doctors who got their registration from 2005-2020 and selected by convenient and snowball sampling. Results: Among 500 female graduate doctors, 428 (85.6%) were involved in different health care services and rest 72 (14.4%) were not involved and among rest 14.4%, about 10% never involved in health care services after completion of their graduation. When 72 respondents female graduate doctors who were not involved asked about their current professions, about one fourth (25%) mentioned they were doing ‘online businesses’, 15.02% were ‘purely housewife’ and 12.5% were ‘changing profession to others’. Among 72 respondents female graduate doctors, one third (33.33%) chose other profession for 'better income'. The most two common reasons for not involving were 'to care children' (39.7%) and 'absence of day care centers' (20.5%). Nearly half (45.5%) of the respondents chose 'establishment of day care / breast feeding centers' when they asked what strategies the government should take to utilize female work force effectively. Conclusions:  Female graduate doctors who were not involved in health system mentioned different reasons behind their decisions and strategies require to be taken by the Government to overcome such conditions.BJME, Volume-16, Issue-01, January 2025: 15-25